Some Operations on Mixed Monotone Operator in Banach Spaces - Badrulfalah Badrulfalah; I Irianingsih; Khafsah Joebaedi (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2018)
This paper discusses some operations on mixed monotone operator in Banach space, especially addition an multiplication operations. We will prove the sum and product of two mixed monotone operators. The proof using some relevant definitions. The result is the sum o of them is a mixed monotone operator and the product is too if both satisfy some conditions